PANDANGAN PEREMPUAN PEKERJA SEBAGAI PENCUCI KELILING (Studi Terhadap Perempuan Pekerja di Jorong Padang Tujuah, Nagari Aua Kuniang, Kecamatan Pasaman, Kabupaten Pasaman Barat) - -, MERISAPUTRI - (Pendidikan Sosiologi, 2014)
This research background overshadow by how view woman of worker in Jorong Padang Tujuah Nagari Aua Kuniang Kecamatan Pasaman Kabupaten Pasaman Barat, this research aim to for describe of view woman of worker as washer around ( study to woman of worker in Jorong Padang Tujuah Nagari Aua Kuniang Kecamatan Pasaman Kabupaten Pasaman Barat.Approach which used in this research that is approach qualitative. With descriptive type. informant this research is housewife to wsher around in Jorong Padang Tujuah Nagari Aua Kuniang Kecamatan Pasaman Kabupaten Pasaman Barat. election of informan at this research use technique of purposive sampling, Kinds of data used is primer data and sekunder data. data collecting technique is observation, interview, documentation. unit analyse is individual is woman of worker as detergent circle. data analysis use principle of miller and of huberman including three phase that is 1. data discount 2. presentation of data 3. conclusion.Result of this research indicate that a. Detergent profile circle in padang Tujuah Nagari Aua Kuniang Kecamatan Pasaman Kabupaten Pasaman Barat generally still under 50 years old from 22 years old until 45 years old, while for level of education of worker around only from level of SD (Elementary School), SMP (Junior High School), and SMA (Senior High School) b. View description of woman worker to detergent circle to be seen from aspect: (1) Work as washer around in general view woman of worker as washer around to its work that is do not need diploma and high education, do not need job experience, can do around house, and this work to helping husband in fulfilling requirement of economics family. ( 2) Allocation in working, view washer around for the allocation of in working become washer around not many confiscating time, only around 3 until 6 oâclock. ( 3) Fee detergent circle, view washer around to accepted fee can assist requirement of economics family around Â± Rp 250.000 until Â± Rp 400.000